Asbestos related diseases from environmental exposure to crocidolite in Da-yao, China. I. Review of exposure and epidemiological data. (1st January 2003) - Luo, S; Liu, X; Mu, S; Tsai, S P; Wen, C P
Abstract : Background: Scattered patches of crocidolite, one form of asbestos, were found in the surface soil in the rural county of Da-yao in southwestern China. In 1983, researchers from the West China University of Medical Sciences (WCUMS) discovered that residents of two villages in Da-yao had hyperendemic pleural plaques and excessive numbers of pleural mesotheliomas. Aims: To review and summarise epidemiological studies, along with other relevant data, and to discuss the potential contribution to environmental risk assessment. Methods: This report is based on a review of several clinical/epidemiological studies conducted by WCUMS researchers since 1984, which included one cross sectional medical examination survey, one clinical/pathological analysis of 46 cases of mesothelioma, and three retrospective cohort mortality studies. Additional information acquired from reviewing original data first hand during a personal visit along with an interview of medical specialists from Da-yao County Hospital was also incorporated. Results: The prevalence of pleural plaque was 20% among peasants in Da-yao over 40 years of age in the cross sectional survey. The average number of mesothelioma cases was 6.6 per year in the 1984–95 period and 22 per year in the 1996–99 period, in a population of 68 000. For those mesothelioma cases that were histology confirmed, there were 3.8 cases/year in the first period and 9 cases/year in the second. Of the 2175 peasants in this survey, 16 had asbestosis. Lung cancer deaths were significantly increased in all three cohort studies. The annual mortality rate for mesothelioma was 85 per million, 178 per million, and 365 per million for the three cohort studies, respectively. The higher exposed peasants had a fivefold increased mesothelioma mortality compared to their lower exposed counterparts. There were no cases of mesothelioma in the comparison groups where no crocidolite was known to exist in the environment. In the third cohort study, almost one of five cancer deaths (22%) was from mesothelioma. The ratio of lung cancer to mesothelioma deaths was low for all three studies (1.3, 3.0, and 1.2, respectively). Conclusions: The observation of numerous mesothelioma cases at Da-yao was a unique finding, due mainly to their lifetime exposure to crocidolite asbestos. The finding of cases dying at a younger age and the relatively high ratio of mesothelioma cases to lung cancer could also be another unique result of lifetime environmental exposure to crocidolite asbestos. Although the commercial use of crocidolite has been officially banned since 1984, the incidence of mesothelioma has continued to show a steady increase, particularly among peasants. Since the latency of mesothelioma is approximately 30–40 years, the ban had little effect in the 1990s. The increased awareness and changes in diagnosis over time may also contribute to the increase. Furthermore, exposure to asbestos stoves and walls continued. The government implemented reduction of these exposures. However, from a public health standpoint, the most important issue is the complete avoidance of further exposure to asbestos.